The Role of Immunomodulatory Nutrients in Alleviating Complications Related to SARS-CoV-2: A Scoping Review. Issue 2 (21st December 2021) - Jandaghi, Parisa; Hosseini, Zeinab; Chilibeck, Philip; Hanley, Anthony J; Deguire, Jason R; Bandy, Brian; Pahwa, Punam; Vatanparast, Hassan
ABSTRACT: The recent coronavirus disease 2019 (COVID-19) pandemic has warranted the need to investigate potential therapies or prophylaxis against this infectious respiratory disease. There is emerging evidence about the potential role of nutrients on COVID-19 in addition to using medications such as hydroxychloroquine and azithromycin. This scoping review aims to explore the literature evaluating the effect of immunomodulatory nutrients on the outcomes including hospitalization, intensive care unit admission, oxygen requirement, and mortality in COVID-19 patients. A literature search of databases including Medline, EMBASE, CINAHL, Web of Science, Cochrane, Scopus, and PubMed, as well as hand-searching in Google Scholar (up to 10 February 2021) was conducted. All human studies with different study designs and without limitation on publication year were included except for non-English-language and review articles. Overall, out of 4412 studies, 19 met our inclusion criteria. Four studies examined the impact of supplementation with vitamin C, 4 studies – zinc, 8 studies – vitamin D, and 3 studies investigated the combination of 2 (zinc and vitamin C) or 3 (vitamin D, vitamin B-12, and magnesium) nutrients. Although limited data exist, available evidence demonstrated that supplementation with immune-supportive micronutrients such as vitamins D and C and zinc may modulate immunity and alleviate the severity and risk of infection. The effectiveness of vitamin C, vitamin D, and zinc on COVID-19 was different based on baseline nutrient status, the duration and dosage of nutrient therapy, time of administration, and severity of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) disease. This review indicated that supplementation with high-dose vitamin C, vitamin D, and zinc may alleviate the complications caused by COVID-19, including inflammatory markers, oxygen therapy, length of hospitalization, and mortality; however, studies were mixed regarding these effects. Further randomized clinical trials are necessary to identify the most effective nutrients and the safe dosage to combat SARS-CoV-2. Abstract : Statement of Significance : Current knowledge about the efficacy of nutrients as supplementary therapy for COVID-19 disease has been compiled up to 10 February 2021. This review aims to provide timely, comprehensive, and continuously updated evidence available on the role of immunomodulatory nutrients regarding one of the most important health issues in the world over the past 18 months. To our knowledge, this review is the first attempt that outlines evidence and knowledge gaps recognizing the need for future studies on the role of nutrients in SARS-CoV-2.